2009
DOI: 10.1111/j.1540-6261.2009.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Trading Costs and Returns for U.S. Equities: Estimating Effective Costs from Daily Data

Abstract: The effective cost of trading is usually estimated from transaction-level data. This study proposes a Gibbs estimate that is based on daily closing prices. In a validation sample, the daily Gibbs estimate achieves a correlation of 0.965 with the transactionlevel estimate. When the Gibbs estimates are incorporated into asset pricing specifications over a long historical sample (1926 to 2006), the results suggest that effective cost (as a characteristic) is positively related to stock returns. The relation is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
531
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 938 publications
(554 citation statements)
references
References 61 publications
16
531
1
6
Order By: Relevance
“…Stoll (2000) found that the spread protects market makers against losses from trade with informed investors; thus, they expand the spread in order to limit informed traders and limit the spread to attract liquidity traders. Hasbrouck (2009) found a relatively high correlation between various spread measures (~90%). Richardson (2000), Mohd (2005), Attig et al (2006), Jayaraman (2008 and Bhattacharya et al (2009) used different spread indices to measure information asymmetry.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Stoll (2000) found that the spread protects market makers against losses from trade with informed investors; thus, they expand the spread in order to limit informed traders and limit the spread to attract liquidity traders. Hasbrouck (2009) found a relatively high correlation between various spread measures (~90%). Richardson (2000), Mohd (2005), Attig et al (2006), Jayaraman (2008 and Bhattacharya et al (2009) used different spread indices to measure information asymmetry.…”
Section: Literature Reviewmentioning
confidence: 91%
“…However, gathering the data required to run this particular version of the model becomes a difficult process as trade direction data is also required. Hasbrouck (2004Hasbrouck ( , 2009 suggests that a more accurate spread can be achieved through employing Gibbs estimation. Unlike Roll's approach a The bias arises as the assumption that returns are random is not satisfied.…”
Section: Relevant Bid-ask Spread Estimatorsmentioning
confidence: 99%
“…The BL model shows that the corrected estimated spread allows for the maximisation of the covariance of the mid-price. The BL estimator is distinctive in that it outperforms Roll (1984), Huang and Stoll (1997), Corwin and Schultz (2012) and Hasbrouck (2009) estimators, following extensive testing.…”
Section: The Sophisticated High-low Estimatormentioning
confidence: 99%
“…22 For a discussion on liquidity measurement see Beber andPagano (2008), Fleming (2003), Bao et al, (2008), Goyenko et al (2009), Sarr and Lybek (2002), Lesmond et al (1999), Hasbrouck (2004Hasbrouck ( , 2009) and Lesmond (2005). Among the most recent contributions, based on the principal component analysis, see Nielsen et al (2012), who obtain an efficient proxy of liquidity by using four indicators: Amihud (2002), implicit trading costs, turnover and zero-trade days proxies.…”
Section: Liquidity Of the Italian Dual-listed Corporate Bondsmentioning
confidence: 99%